2014
DOI: 10.1371/journal.pntd.0002722
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Approaches That Slow Lymphatic Flow As a Snakebite First Aid

Abstract: BackgroundThis study examines the use of topical pharmacological agents as a snakebite first aid where slowing venom reaching the circulation prevents systemic toxicity. It is based on the fact that toxin molecules in most snake venoms are large molecules and generally first enter and traverse the lymphatic system before accessing the circulation. It follows on from a previous study where it was shown that topical application of a nitric oxide donor slowed lymph flow to a similar extent in humans and rats as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
5
21
0
2
Order By: Relevance
“…Another study demonstrated a slowing of lymph flow in rats after the application of the local anaesthetic lignocaine, which was also attributed to an inhibition of nerves (van Helden et al . ). Such an observation can also partly result from a direct LSMC effect because isolated rat lymphatic vessels reduce the contraction frequency when VGSC are blocked, and lymphatic vessels from sheep, which are known to express VGSC in the LSMC, reduce the lymphatic pumping in the presence of VGSC blockade (Zawieja et al .…”
Section: Discussionmentioning
confidence: 97%
“…Another study demonstrated a slowing of lymph flow in rats after the application of the local anaesthetic lignocaine, which was also attributed to an inhibition of nerves (van Helden et al . ). Such an observation can also partly result from a direct LSMC effect because isolated rat lymphatic vessels reduce the contraction frequency when VGSC are blocked, and lymphatic vessels from sheep, which are known to express VGSC in the LSMC, reduce the lymphatic pumping in the presence of VGSC blockade (Zawieja et al .…”
Section: Discussionmentioning
confidence: 97%
“…One such study reported the use of rats as a proxy for humans to study a novel first aid treatment for snake envenomations. 37 2. This discrepancy may result from differences in the source and composition of ginkgo products.…”
Section: Discussionmentioning
confidence: 99%
“…Larger venom molecules reach the systemic circulation mainly by lymphatic transport. Lidocaine (1 g/l) and verapamil at safe dosages and concentrations are known to impair lymphatic smooth muscle function and slow lymphatic transport of large protein molecules toward the thoracic duct and the systemic circulation . Future studies are needed to investigate the efficacy of lidocaine and verapamil against lymphatic transport of larger snake venom molecules.…”
Section: Discussionmentioning
confidence: 99%